The changes in saliva cotinine during Ramadhan among a group of Muslim smokers in Malaysia - Zulkifley, Nuraisyah Hani; Ismail, Suriani; Abdul Manaf, Rosliza (Medip Academy, 2017)
Background: Smoking is a negative health behaviour that brought in health and social problems into the community. The effects of smoking can be decreased by promoting smoking cessation. One of the approaches in smoking cessation intervention focuses on the supportive environment that can be naturally found during the Ramadan where every Muslim is obligated to fast which included abstaining from smoking.Methods:A total of 61 male, Muslim smokers who currently smoke cigarette on daily basis were recruited. The study was conducted by using the one-group pretest-posttest study design to evaluate the effect of Ramadan environment on saliva cotinine among a group of smokers who work at a local authority in Selangor. The data were collected three times which were one week before Ramadan, 21st of Ramadan and 21 days after Ramadan. The saliva cotinine were measured by using SalivaBio oral swab (SOS) and cotinine biomarker research salivary assay kits and protocols by Salimetrics with the sensitivity of 0.15ng/ml. Data analysis was conducted by using One-way ANOVA with repeated measures and paired t-test.Results: The study showed a significant difference in the saliva cotinine level from before, during and after Ramadan (p = 0.002). From the post-hoc test, there is a significant positive changes in the saliva cotinine level from before Ramadan to during Ramadan (t (60) = 3.66, p = 0.001).Conclusions:The saliva cotinine level of the smokers decreased during Ramadan. This can provide an opportunity for easier initiation of smoking cessation for the smokers.